Námět v díle současných českých malířů a jeho vztah k osobnosti tvůrce - Uholyeva, Xenie (2009)
The construed diploma thesis deals with both some content characteristics of the visual artist's work and his/her individuality (personality) as well as their correlation. The theoretical part of the thesis begins with an introduction to the issues in the interdisciplinary research in creative art. In the second chapter, a summary of present research focused on visual artist's personality as well as on personality correlates of creativity in general and on some typologies of artists which impeach their production and personality is included. Our personal results are later compared with those studies. The third chapter is attended to the subjects in creative art. We treat of the subject like the aspect of artist's production which can bring psychological information on the artist. The production process in light of the genesis of the subject is described. We also deal with an influence of the subject on perception of art artifact. In the fourth chapter, the research of Stanislav Drvota which we are repeating in the altered form in the empiric part is briefly described. In the experimental part, we are describing artists' personality characteristics per personage questionnaires. The content characteristics are evaluated via the experimental tool taken over from Drvota. At the last part, artist's personality...